Catalytic Polarographic Determination of Microgram Quantities of Zinc(II - Uma Mahesh, M.; Sreenivasulu, M.; Suryanarayana Rao, V. (Asian Journal of Chemistry, 2010)
A simple and sensitive polarographic method is developed for the determination of microgram quantities of zinc(II) based on the catalytic reduction of iodate. Salicylaldehyde thiosemicarbazone causes enhancement in current thus making the method more sensitive.